2021
DOI: 10.1177/03091333211001793
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and seasonal patterns of rainfall erosivity in the Lake Kivu region: Insights from a meteorological observatory network

Abstract: In the Lake Kivu region, water erosion is the main driver for soil degradation, but observational data to quantify the extent and to assess the spatial-temporal dynamics of the controlling factors are hardly available. In particular, high spatial and temporal resolution rainfall data are essential as precipitation is the driving force of soil erosion. In this study, we evaluated to what extent high temporal resolution data from the TAHMO network (with poor spatial and long-term coverage) can be combined with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In this call for data, contributors from Poland, Slovenia, Uruguay and the Democratic Republic of Congo (DRC) responded with data from 314 new stations. The contribution from DRC is very important, as the R-factor data are very limited for Africa [9] . Finally, the updated GloREDa 1.2 includes 3939 stations ( Fig.…”
Section: Data Descriptionmentioning
confidence: 99%
“…In this call for data, contributors from Poland, Slovenia, Uruguay and the Democratic Republic of Congo (DRC) responded with data from 314 new stations. The contribution from DRC is very important, as the R-factor data are very limited for Africa [9] . Finally, the updated GloREDa 1.2 includes 3939 stations ( Fig.…”
Section: Data Descriptionmentioning
confidence: 99%
“…Tropical ecosystems are especially affected by erosion because of high precipitation rates and intensities (Bagalwa et al, 2021;Labrière et al, 2015). The Congo Basin is home to some of the most pristine tropical and subtropical forests, covering distinct forest types.…”
Section: Introductionmentioning
confidence: 99%
“…The Congo Basin is home to some of the most pristine tropical and subtropical forests, covering distinct forest types. While the erosion potential is high in montane forests in the eastern parts of the Congo basin because of the combination of high rainfall erosivity and steep topography (Bagalwa et al, 2021), physical erosion is reported to be much lower in the dense lowland forests in the central part of the basin (Borrelli et al, 2017). In contrast to both the montane and lowland forests, the subtropical Miombo woodlands in the south of the Congo Basin have a sparser vegetation cover (especially during the dry season, where the understory vegetation is lost to seasonal fires) compared to other tropical forests, leaving their surface layers less protected against heavy rainfall.…”
Section: Introductionmentioning
confidence: 99%